2009
DOI: 10.1017/s0007114508201959
|View full text |Cite
|
Sign up to set email alerts
|

Long-term association of food and nutrient intakes with cognitive and functional decline: a 13-year follow-up study of elderly French women

Abstract: The objective of the present study was to determine the potential long-term impact of dietary habits on age-related decline among 4809 elderly women (born between 1925 and 1930) in the 'Etude Epidémiologique de Femmes de la Mutuelle Générale de l'Education Nationale' (E3N) study, a French epidemiological cohort. In 1993, an extensive diet history self-administered questionnaire was sent to all participants, and in 2006 another questionnaire on instrumental activities of daily living (IADL) and recent cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
7
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 30 publications
5
140
7
1
Order By: Relevance
“…Among prospective studies, intake of dairy products, fruits and vegetables were inversely associated with risk of disability in IADL and ADL over time, mainly in women [9,15]. No association with other food groups was reported in these analyses.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Among prospective studies, intake of dairy products, fruits and vegetables were inversely associated with risk of disability in IADL and ADL over time, mainly in women [9,15]. No association with other food groups was reported in these analyses.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the lack of assessment of disability in IADL and ADL at baseline in these studies, which constituted a major drawback, results are in agreement with a potential benefit role of particular food groups in the disablement process. Concerning dietary micronutrient intake, women of the E3N study with IADL impairment reported past lower intakes of vitamins B6 and B12 [15]. Biological data confirm these findings since low serum concentration of vitamins B6 and B12, were significant and independent predictors of ADL disability 3 years later in women enrolled in the Women"s Health and Aging Study while carotenoids, zinc and folate levels, which are also yet common in the MeDi, were not significant predictors [10].…”
Section: Discussionmentioning
confidence: 75%
“…In addition to deficiency-associated diseases, there is concern with regard to the disease risks associated with sub-optimal intakes as low intake of certain micronutrients has been implicated in multi-factorial diseases such as cancer, heart disease and cognitive decline, especially in the elderly when food intakes fall and micronutrient intake can become critical (1)(2)(3) . However, despite some evidence suggesting the possible benefits of increased intake of micronutrients such as folate, selenium (Se), carotenoids, vitamin B 12 and vitamin D, for some micronutrients the benefits of supplementation have not been proven and indeed in some cases there is evidence that raising intake by supplementation may increase disease risk.…”
Section: Selenium: Selenoproteins: Gene Microarray: Single-nucleotidementioning
confidence: 99%
“…49 No entanto nesta população os valores da razão não excedem 3.0. A pouca variabilidade (limites: 1,14 -2,95) neste índice talvez possa ser explicada pela alimentação essencialmente de tipo mediterrânico, com consumo frequente de vegetais, carnes de animais criados ao ar livre e consumo de peixe.…”
Section: Discussionunclassified